Proteome-wide alterations in an industrial clavulanic acid producing strain of Streptomyces clavuligerus - Ünsaldı, Eser; Kurt-Kızıldoğan, Aslıhan; Voigt, Birgit; Becher, Dörte; Özcengiz, Gülay (Synthetic and systems biotechnology, 2017)
The usefulness of genetic/metabolic engineering for further improvement of industrial strains is subject of discussion because of the general lack of knowledge on genetic alterations introduced by iterative cycles of random mutagenesis in such strains. An industrial clavulanic acid (CA)-overproducer Streptomyces clavuligerus DEPA was assessed to understand proteome-wide changes that have occurred in a local industrial CA overproducer developed through succesive mutagenesis programs. The proteins that could be identified corresponded to 33 distinct ORFs for underrepresented ones and 60 ORFs for overrepresented ones. Three CA biosynthetic enzymes were overrepresented in S. clavuligerus DEPA; carboxyethylarginine synthase (Ceas2), clavaldehyde dehydrogenase (Car) and carboxyethyl-arginine beta-lactam-synthase (Bls2) whereas the enzymes of two other secondary metabolites were underrepresented along with two important global regulators [two-component system (TCS) response regulator (SCLAV_2102) and TetR-family transcriptional regulator (SCLAV_3146)] that might be related with CA production and/or differentiation. γ-butyrolactone biosynthetic protein AvaA2 was 2.6 fold underrepresented in S. clavuligerus DEPA. The levels of two glycolytic enzymes, 2,3-bisphosphoglycerate-dependent phosphoglycerate mutase and phosophoglycerate kinase were found decreased while those of dihydrolipoyl dehydrogenase (E3) and isocitrate dehydrogenase, with two isoforms were found as significantly increased. A decrease of amino acid metabolism, methionine biosynthesis in particular, as well as S-adenosylmethionine synthetase appeared as one of the prominent mechanisms of success of S. clavuligerus DEPA strain as a prolific producer of CA. The levels of two enzymes of shikimate pathway that leads to the production of aromatic amino acids and aromatic secondary metabolites were also underrepresented. Some of the overrepresented stress proteins in S. clavuligerus DEPA included polynucleotide phosphorylase/polyadenylase (PNPase), ATP-dependent DNA helicase, two isoforms of an anti-sigma factor and thioredoxin reductase. Downregulation of important proteins of cell wall synthesis and division was recorded and a protein with β-lactamase domain (SCLAV_p1007) appeared in 12 isoforms, 5 of which were drastically overrepresented in DEPA strain. These results described herein provide useful information for rational engineering to improve CA production in Streptomyces clavuligerus.